Pattern edges improve predator learning of aposematic signals. (23rd July 2018) - Green, Naomi F; Urquhart, Holly H; van den Berg, Cedric P; Marshall, N Justin; Cheney, Karen L
Abstract : Many animals use body patterns, such as stripes and spots, to prevent them from being detected by predators or prey, or to highlight that they are toxic and should be avoided. Using behavioral experiments with fish, our study finds that color patterns that contain a larger amount of pattern edge enables predators to learn to avoid warning signals more quickly. Abstract: Edges are salient visual cues created by abrupt changes in luminance and color and are crucial in perceptual tasks such as motion detection and object recognition. Disruptively colored animals exploit edge detection mechanisms to obscure their body outline and/or to conceal themselves against their background. Conversely, aposematic species may use contrasting patterns with well-defined edges to create highly salient, memorable warning signals. In this study, we investigated how the amount of internal pattern edge, colored area, pattern type, or shape repetition of warning signals influenced avoidance learning in the triggerfish, Rhinecanthus aculeatus. Using 6 different warning signals, we found that fish learnt to avoid aposematic signals faster when they featured more internal pattern edge. We found little evidence that the amount of colored area or pattern type affected learning rates. An optimal amount of pattern edge within a warning signal may therefore improve how warning signals are learnt. These findings offer important insights into the evolution of prey warning signal evolution and predator psychology.